POLITICAL THOUGHT OF LUKA ZRNIĆ - Nadoveza, Branko (Political Review, 2023)
Luka Zrnić wrote several works, mostly scientific brochures, which are on the border between journalism and science. They do not have a special scientific contribution, but they are significant because they were created at the beginning of the 20th century. In his works on democracy, religion, state, and institutions, L. Zrnić supports modernity over tradition and conservatism. He is a legitimist and a pacifist by definition. He is not a supporter of the social democratic idea, which at that time had features of communist ideology and aspirations towards revolution and the abolition of private property. According to him, society must have a link between labor and capital. He was pessimistic about the drowning of the Serbian people in the Yugoslav state, considering that there were great historical differences between Serbs, Croats, and Slovenes.
Keywords: Luka Zrnić; politics; democracy; Vidovdan constitution; Serbia; history; world war; state; religion; tradition